The Role of The Financial Services Authority in The Legal Protection of Privacy Rights in Connection with Personal Data of Fintech Lending Debtor in Indonesia - Intan Audia Priskarini; Pranoto .; Kukuh Tejomurti (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
The speed of disbursement of funds also makes fintech lending seems easy. Consequently, many people are interested to make credit. There are more than 900 alleged violations of law and human rights by online funding applications, including alleged violations of the privacy rights of the debtor’s personal data where billing is submitted not only to the debtor but also to all telephone contacts stored on the debtor’s cellphone without consent. This study is a prescriptive normative study through library research to look for secondary data by using primary, secondary, and tertiary legal materials and field researches. The study reveals several results. Firstly, although the Regulation of the Financial Services Authority Number 77 of 2016 has been published, fintech providers registered in the Financial Services Authority have not upheld a legal culture to protect debtors on the use of debtors’ personal data. Secondly, fintech lending makes it easier for Indonesian people to have a positive impact due to the speed of the application fund disbursement system but this convenience is not matched by the knowledge of debtors who do not read and pay attention to the contents of electronic contracts. Thirdly, as long as the Personal Data Protection Bill has not been ratified, as a preventive measure, the Financial Services Authority can take some alternative roles, namely Financial Services Authority should be involved in reviewing electronic contracts made by fintech lending and giving feasible recommendations on electronic contracts made by parties and standardize electronic contract contents so that each fintech lending company has the same and clear contract contents set by the Financial Services Authority.Peran Otoritas Jasa Keuangan (OJK) dalam Perlindungan Hukum Hak Privasi atas Data Pribadi Konsumen Peminjam Fintech Lending di IndonesiaAbstrakKecepatan pencairan dana membuat peminjaman fintech tampak mudah. Akibatnya, banyak orang tertarik untuk memberikan kredit. Ada lebih dari 900 dugaan pelanggaran hukum dan hak asasi manusia oleh aplikasi pendanaan online, termasuk dugaan pelanggaran hak privasi data pribadi debitur di mana penagihan diajukan tidak hanya kepada debitur tetapi juga ke semua kontak telepon yang disimpan di ponsel debitur tanpa persetujuan. Penelitian ini adalah penelitian normatif preskriptif melalui penelitian kepustakaan untuk mencari data sekunder dengan menggunakan bahan hukum primer, sekunder, dan tersier serta penelitian lapangan. Studi ini mengungkapkan beberapa hasil. Pertama, meskipun Peraturan Otoritas Jasa Keuangan No. 77 tahun 2016 telah diterbitkan, penyedia fintech yang terdaftar di Otoritas Jasa Keuangan belum menegakkan budaya hukum untuk melindungi debitur dalam penggunaan data pribadi debitur. Kedua, pinjaman fintech memudahkan orang Indonesia untuk memiliki dampak positif karena kecepatan sistem pencairan dana aplikasi tetapi kemudahan ini tidak diimbangi dengan pengetahuan debitur yang tidak membaca dan memperhatikan isi kontrak elektronik. Ketiga, selama RUU Perlindungan Data Pribadi belum disahkan, sebagai tindakan pencegahan, Otoritas Jasa Keuangan dapat mengambil beberapa peran alternatif, yaitu Otoritas Jasa Keuangan harus dilibatkan dalam meninjau kontrak elektronik yang dibuat oleh pinjaman fintech dan memberikan rekomendasi yang layak tentang kontrak elektronik dibuat oleh para pihak dan membuat standar konten kontrak elektronik sehingga setiap perusahaan pemberi pinjaman fintech memiliki isi kontrak yang sama dan jelas yang ditetapkan oleh Otoritas Jasa Keuangan.Kata kunci: Fintech, Pelanggaran, PrivasiDOI: https://doi.org/10.22304/pjih.v6n3.a7